Pengaruh Kepemimpinan Transformasional dan Motivasi terhadap Kinerja Sumber Daya Manusia di Universitas Cokroaminoto Yogyakarta - Mony, Gadhan; Rinaldi (Journal of Economics, Business, Accounting and Management, 2024)
The research aims to analyze the Influence of Transformational Leadership, on the Motivation and Performance of Human Resources with the research object of all students of Cokroaminoto University Yogyakarta. This research is a quantitative research. The sample used in the study was 100 respondents. The research uses the Statistical Product and service solutions program with SPSS software version 25. The results of this study are as follows. Partially, Transfoemional Leadership has a significant effect on Human Resources Performance by marking a t-count value of 3.839 greater than the t-table of 1.985. Motivation partially had a significant effect on Human Resource Performance by marking the t-count value of 4.429 smaller than the t-table 1.985. Simultaneously, Transformational Leadership, and Motivation have a significant effect on Human Resources Performance. This study aims to determine the partial and simultaneous influence of Transformational Leadership and Motivation on Human Resource Performance at Cokroaminoto University Yogyakarta. In addition, in order to continue to supervise the level of student discipline, especially during study hours and to further increase the motivation of students.